International Configuration and Coordination Archetypes for Medium-Sized Firms in Global Industries - Roth, Kendall (Journal of International Business Studies, 1992)
The purpose of this study is to determine the basic configuration and coordination patterns for medium-sized firms competing in global industries. Analyzing 126 businesses competing in nine different global industries, five distinct archetypes are identified. The results suggest that selective globalization—in which the firm defines its global strategy around a narrow subset of the value chain—may lead to the most effective outcomes.